In situ crude protein and starch degradation and in vitro evaluation of pea grains for ruminants. Issue 6 (2nd November 2021) - Titze, Natascha; Krieg, Jochen; Steingass, Herbert; Rodehutscord, Markus
ABSTRACT: Thirteen pea grain samples from different origins were used to examine the variation in in situ ruminal degradation of crude protein (CP) and starch as well as in vitro gas production (GP) kinetics. In vitro GP was used to estimate the digestibility of organic matter (dOM), metabolisable energy (ME) and utilisable CP at the duodenum (uCP). Protein fractions were also determined according to the Cornell Net Carbohydrate and Protein System. Degradation of CP and starch from all pea grains in the rumen was almost complete, with a high proportion of the instantly disappearing fraction. The variation in the degradation constants among pea grain variants was high, and degradation of CP and starch showed a significant initial lag phase in the rumen. The mean effective degradation (ED) calculated for a rumen outflow of k = 8%/h of CP (EDCP8) was higher than ED of starch (EDST8), averaging 77.0 and 71.5%, respectively, with low variation among variants. A correlation analysis between GP parameters and in situ degradation constants showed no clear relationship, but the rates of in vitro GP and in situ starch degradation were similar. Most of the protein in the pea grains was buffer-soluble with fast and intermediate degradation. Variation in the protein fractions among the pea grain variants was low and not suitable for predicting differences in in situ degradation characteristics. The mean in vitro uCP of pea grains was 198 g/kg dry matter (k = 8%/h) and variation was low and consistent with that of GP kinetics and in situ rumen undegradable crude protein values. The estimation of dOM and ME from 24 h GP led to very high values indicating that the existing prediction equations may not be suitable for pea grains as a single feed.